(untitled) (Acta Scientiarum. Agronomy, 2023)
Curves of crop growth and nutrient extraction and export are essential to develop fertilization strategies and management plans to maximize yield and reduce environmental impacts. Our study aimed to evaluate dry matter production and both extraction and export of macronutrients by arrowroots (Maranta arundinacea L.) to be used in further crop fertilization plans. To this purpose, two experiments were carried out in field conditions using the varieties Viçosa and Seta. The experimental design was randomized with four replications and nine periods of analysis, which were defined as days after planting (105, 135, 165, 195, 225, 255, 285, 315, and 345 DAP). Dry matter, extraction, and export of macronutrients by arrowroot seed-rhizomes, aerial parts, roots, and storage roots (rhizomes) were determined. The exports of N, P, K, Ca, Mg, and S of storage rhizomes of the variety Viçosa were 104.6, 51.83, 412.24, 15.85, 36.14, and 64.36 kg ha-1, while those of the seta variety were 160.6, 71.62, 521.31, 17.57, 60.09, and 160.41 kg ha-1, respectively. Both varieties proved to be efficient soil macronutrient extractors, mainly for K. The variety Seta had higher shoot, root, seed-rhizome dry matter contents, as well as greater macronutrient extractions and exports.